Barriers and Facilitators of Pharmacists’ Roles During the Pandemic in Malaysia - Palani Velu, Thanushiri; Islahudin, Farida; Chong, Wei Wen (UI Scholars Hub, 2024)
Background: The coronavirus disease 2019 (COVID-19) left a devastating impact on healthcare systems worldwide. The crisis initially emerged as a supply disruption issue but eventually evolved into a myriad of additional challenges, which were attributed mainly to the extensive scale of the pandemic. This study aimed to explore the barriers to the role of hospital pharmacists and related facilitators encountered during the COVID-19 pandemic. Methods: Pharmacists in Malaysia participated in a cross-sectional online questionnaire-based survey. The participants were recruited using convenient sampling. Cronbach alpha of the questionnaire was analyzed. Results: The study successfully enrolled 367 pharmacists. The major barrier in terms of knowledge and skills was the difficulty in investigating the trend and usage pattern of COVID-19 medicines (N = 183; 49.9%). A global shortage of medicines (N = 314; 85.6%) occupied the highest barrier in the supply chain. The clinical barriers cited by most of the respondents comprised conducting clinical trials in the search for effective treatments (N = 282; 76.8%), and the largest departmental barrier was the difficulty of predicting usage based on previous data (N = 262; 71.4%). Almost all respondents agreed that a course or module on COVID-19 treatments (N = 354; 96.5%) served as a facilitator, enhancing their awareness and preparedness to respond to the pandemic. Conclusions: The empowerment of pharmacists with the crucial resources, skills, and support that will enable them to effectively fulfill their roles and responsibilities can be instrumental in the transformation of our approach to addressing future pandemics.